Mathematical Journals and Teacher Audiences (18th – 20th centuries). The Heuristic Role of the Heterogeneity of Mathematics Education Worlds - Gispert, Hélène (Swiss Journal of Educational Research, 2018)
Putting on their agenda the study of the various mathematical practices of a time, historians focused on the mechanisms of circulation – a part of the study of the production process of mathematics as such – of which teaching is one of the particular forms. By the study of journals addressed to teachers, their editorial projects, their readership and their authorship, we will try to grasp mathematics as practiced by the actors of different school spheres in the Europe of the 18th to 20th centuries. It appears that the diverse teacher audiences themselves become producers of the published mathematical knowledge, questioning the traditional partitions between scholarly knowledge and school knowledge, scholarly spheres and school spheres.